КОНЦЕПЦИЯ ПЛАНАЦИИ РЕЛЬЕФА И ПРОБЛЕМА ПОВЕРХНОСТЕЙ ВЫРАВНИВАНИЯ АЛЬПИЙСКИХ ГОРНЫХ СООРУЖЕНИЙ (НА ПРИМЕРЕ МАЛОГО КАВКАЗА) - Халилов Г.А. (My University, 2003)
The paper considers problems of planation surfaces in Alpine mountains from the standpoint of abrasion-strati-graphic concept of the relief planation, as developed by the author. According to the concept, origin of planation surfaces is associated with abrasion activity of marine basins, the age and number of the surfaces being related to age and quantity of transgressive unconformities in lithofacies. In the light of the new ideas, the author recognizes 7 surfaces of planation in the Lesser Caucasus dated to interval beginning with Oxfordian-Tithonian and ending at Late Pliocene-Pleistocene.
Keywords: Pleistocene; Pliocene; Tithonian; Oxfordian; 551.435.21(-924.76); Cenozoic::Quaternary::Pleistocene; Мезозой::Юрская::Верхний::Титонский; Мезозой::Юрская::Верхний::Оксфордский; Cenozoic::Neogene::Pliocene; Кайнозой::Четвертичная::Плейстоцен; Кайнозой::Неоген::Плиоцен; Mesozoic::Jurassic::Upper::Tithonian; Mesozoic::Jurassic::Upper::Oxfordian